THE ROLE MEDIATION INNOVATION-BASED PUBLIC SERVICES: ORGANIZATIONAL CULTURE TOWARD EMPLOYEE PERFORMANCE: THE ROLE MEDIATION INNOVATION-BASED PUBLIC SERVICES: ORGANIZATIONAL CULTURE TOWARD EMPLOYEE PERFORMANCE - Putri, Zhelika Nurul; Seswandi, Agus; Supeno, Bambang (PENANOMICS: International Journal of Economics, 2025)
Organizational culture plays a very important role in shaping the identity and excellence of an organization, both in the public and private sectors. An organizational culture that supports openness, collaboration, and risk-taking can accelerate the innovation process and enable organizations to be more adaptive to change and create new products and services that meet the needs of society; a strong culture that is aligned with organizational strategy can improve employee performance. This study aims to examine the mediating role of innovation-based public services: organizational culture and employee performance of the Siak Regency Regional Secretariat. This study uses a quantitative method by distributing questionnaires via Google Forms to 100 people. Data is processed using SmartPLS 3.2.9 software. The data analysis method uses structural equation modeling-partial least square (SEM-PLS). The results of the study indicate that organizational culture has a positive and significant effect on innovation-based public services, and innovationbased public services has a positive and significant effect on employee performance. Organizational culture has a positive and significant effect on employee performance. Innovation-based public services is able to mediate the influence between organizational culture and employee performance. In conclusion, the influence between organizational culture, innovation-based public services, and employee performance is still growing. By understanding the mechanisms underlying this relationship, the Siak Regency Regional Secretariat can design more effective service programs to improve employee innovation and performance